Cyclin E1 and Rb modulation as common events at time of resistance to palbociclib in hormone receptor-positive breast cancer. (December 2018) - Guarducci, Cristina; Bonechi, Martina; Benelli, Matteo; Biagioni, Chiara; Boccalini, Giulia; Romagnoli, Dario; Verardo, Roberto; Schiff, Rachel; Osborne, C.; De Angelis, Carmine; Di Leo, Angelo; Malorni, Luca; et al.
Abstract CDK4/6 inhibitors represent a new treatment standard for hormone receptor-positive (HR+), HER2-negative advanced breast cancer (BC) patients. Although efficacious, resistance to these agents is universal. Here, we profiled a large panel of HR+ BC cell lines with conditioned resistance to the CDK4/6 inhibitor palbociclib, and analyzed cell cycle-related markers by gene expression profiles (GEP) and western blot (WB). GEP showed high molecular heterogeneity among the models, with E2F targets being significantly enriched both during treatment and at the time of resistance. By both WB and GEP, a common molecular feature at the time of palbociclib resistance was the concomitant overexpression of cyclin E1 and down-regulation of Rb.CCNE1 was the only significantly up-regulated gene among E2F targets at resistance withCCNE1 genomic amplification being observed in two resistant models. Rb was downregulated in all resistant models; a reduction ofRB1 copy number was observed in three resistant cell lines. In silico analyses showed thatCCNE1/RB1 ratio correlated with palbociclib IC50 in different datasets of both breast and non-breast cancer cell lines, performing better thanCCNE1 orRB1 taken separately. Finally, theCCNE1/RB1 ratio was shown to be an adverse prognostic factor in patients with ER+ BC and to be able to discriminate palbociclib-sensitive versus resistant among patients enrolled in the NeoPalAna trial, a neoadjuvant trial testing palbociclib, performing better thanCCNE1 orRB1 alone. Our data suggest that theCCNE1/RB1 ratio may be a viable biomarker of palbociclib resistance, warranting further clinical validation. Biomarkers: Prognostic indicator for resistance to cell cycle–targeted drug The expression levels of two genes involved in controlling the cell cycle offers a promising predictive indicator of whether women with hormone receptor–positive breast cancer are likely to develop resistance to the drug palbociclib. A team led by Luca Malorni and Ilenia Migliaccio from the Hospital of Prato, Italy, analyzed gene and protein profiles in a panel of breast cancer cell lines with differential sensitivity to palbociclib. The researchers found that, compared to palbociclib-sensitive cell lines, those that were drug-resistant tended to have elevated expression of one cell-cycle–related gene, calledCCNE1, and reduced expression of another, calledRb . The ratio ofCCNE1:Rb expression proved to be an accurate prognostic factor among patients enrolled in a clinical trial of palbociclib, performing better than eitherCCNE1 orRb levels on their own.